Non-deterministic reef fish community assembly in an upwelling-influenced transitional subprovince of the southwestern Atlantic - Carnaúba, Emily A. A.; Gomes, Lorena de M. J.; Garcia, Gabriel S.; Cordeiro, Cesar A. M. M.; Mendes, Thiago C.; Ferreira, Carlos E. L.; Gherardi, Douglas F. M. (Frontiers in Marine Science, 2023)
There are two major theories for setting up ecological communities, the Niche Theory and the Neutral Theory. Both seek to explain the main factors that form a community, which is a great challenge, since each community has its particularities and the environment has different ways to manifest. We devised a process-oriented study that sought to establish the role of environmental niche driven by coastal upwelling in the assembly of reef fish communities from exposed and sheltered environments a few kilometers apart, in the region of Arraial do Cabo (southwestern Atlantic). A multivariate hierarchical generalized linear mixed model fitted with Bayesian inference was applied to abundance and presence-absence data from visual census, together with environmental data from satellite and reanalysis. We found a stronger contribution of random effects to abundance variance with 24% for sites and 20.7% for sheltered vs. exposed locations, and weaker environmental effects with 7.1% for surface chlorophyll-a concentration (SCC) and 5.4% for sea surface temperature (SST). Environmental effects had a stronger contribution in the presence-absence model, with 20.1% for SCC and 14.6% for SST. The overall influence of the upwelling environment across all species was negative, e.g., Gymnothorax moringa and Canthigaster figueiredoi showing negative responses to SCC and Parablennius pilicornis and Malacoctenus delalandii to SST. The joint action of migration-niche mechanisms is inferred from the dominance of spatio-temporal structure, limited influence of life history traits and phylogeny, explaining around 95% of species niches in the abundance model. Our results bring new evidence for the importance of different filters for community assembly other than the environment, such as phylogenetic history and dispersal. We also discuss the balance between niche (environment) and neutral (stochasticity) processes for the assembly of reef fish communities in a tropical-subtropical transition zone.